2017
DOI: 10.3897/natureconservation.19.12681
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal cline in weapon allometry and phenology of the European stag beetle

Abstract: Animal body size commonly exhibits a remarkable variation in response to environmental conditions. Latitude, when correlated with temperature, rainfall and seasonality, represents one of the main determinants of variation in body size, as well as in allometry. It has long been recognised that populations of larger body size are found in colder environments (Bergmann's Rule), a cornerstone of evolutionary ecology. However, the way in which latitude might influence investment in exaggerated weapons of animals ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 81 publications
0
22
1
Order By: Relevance
“…Although trait variation across geographic regions is a fundamental subject with a long history in evolutionary biology, the processes responsible for geographic variation in sexual traits are still only partially understood (Hasegawa & Arai, 2013 2011; Painting et al, 2014;Romiti et al, 2017). In this study, we ob- hind leg was bigger and the hind tibia relatively slenderer at lower latitudes than at higher latitudes.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Although trait variation across geographic regions is a fundamental subject with a long history in evolutionary biology, the processes responsible for geographic variation in sexual traits are still only partially understood (Hasegawa & Arai, 2013 2011; Painting et al, 2014;Romiti et al, 2017). In this study, we ob- hind leg was bigger and the hind tibia relatively slenderer at lower latitudes than at higher latitudes.…”
Section: Discussionmentioning
confidence: 66%
“…Although trait variation across geographic regions is a fundamental subject with a long history in evolutionary biology, the processes responsible for geographic variation in sexual traits are still only partially understood (Hasegawa & Arai, ; Kelly, Folinsbee, Adams, & Jennions, ; Monteiro & Lyons, ; Outomuro & Johansson, ; Painting et al, ; Romiti et al, ). In this study, we observed remarkable variation in body size, the dimensions of sexually dimorphic hind legs, and their allometric slopes across populations of O. sexualis .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations